Where do KIBS workers work in Germany?: Shifting patterns of KIBS employment in metropoles, regiopoles and industrialised hinterlands - Growe, Anna (Erdkunde, 2016)
In the years following reunification, the polycentric German urban system has undergone changes as regards the location of employees in knowledge-intensive business service (KIBS) professions. For the purposes of analysing functional spatial patterns, those spatial patterns exhibiting above-average increases or decreases in the numbers of employees within KIBS professions were identified on the basis of employment data. Correlations in the spatial affinities within service professions of differing compositions were mapped, leading to the identification of four patterns. Based on these patterns, spatial differentiation arising between the various services in the German urban system has been interpreted as functional specialisation. The basis of functional specialisation, with reference to the concept of knowledge bases, is differentiation into the following three service industries: technological services, consulting services and creative services. In den Jahren nach der Wiedervereinigung konnten im deutschen Städtesystem Veränderungen hinsichtlich der Verortung von Beschäftigten in wissensintensiven Dienstleistungen beobachtet werden. Um funktionale räumliche Muster zu analysieren werden in diesem Beitrag Räume mit überdurchschnittlichen Zu- bzw. Abnahmen der Beschäftigtenzahl in wissensintensiven Dienstleistungsberufen auf der Grundlage von Berufsdaten identifiziert. Zusammenhängende Raumaffinitäten unterschiedlicher Dienstleistungsberufe werden kartographisch dargestellt und zeigen vier Grundmuster der Veränderung. Auf der Grundlage dieser räumlichen Differenzierung wird die Herausbildung funktionaler Spezialisierung im deutschen Städtesystem diskutiert, wobei Dienstleistungen mit Hinblick auf das Wissensbasen-Konzept in drei Bereiche differenziert werden: technische Dienstleistungen, Beratungsdienstleistungen und kreative Dienstleistungen.